Analysis of quality of frozen thawed bull sperms treated with bisphenol A - K BRINDHA; M ARTHI; M PARTHIBAN (Indian Journal of Animal Sciences, 2023)
Bisphenol A is a pervasive endocrine disruptor that causes various detrimental health effects on animals and humans. There are several evidences to support that this persistent chemical affects male fertility by interfering with the process of functional maturation of sperms like motility, hyperactivation, capacitation and acrosome reaction in laboratory species. The present study was aimed to evaluate the effect of BPA on the quality of the frozen thawed sperms in higher animal model namely bull. Frozen thawed bull sperms were exposed to four different concentrations of BPA. Aliquots of sperms from each treatment group were examined at three time periods for assessing acrosome integrity, viability and membrane integrity. Exposure of sperms in vitro to BPA revealed that there is a significant influence of BPA on treatment groups when compared to control. The loss of acrosomal integrity and viability was higher even at as low a concentration of 10 μM BPA. The reduction in sperm quality was proportional to the increase in exposure period. Further in vitro investigation is required to elucidate the mechanism of action of BPA that alters the sperm quality.